1964
DOI: 10.1086/109234
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the third integral of motion: Some numerical experiments

Abstract: The problem of the existence of a third isolating integral of motion in an axisymmetric potential is investigated by numerical experiments. It is found that the third integral exists for only a limited range of initial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
834
0
25

Year Published

1988
1988
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,930 publications
(895 citation statements)
references
References 2 publications
16
834
0
25
Order By: Relevance
“…The following aspects are similarly found in the paradigmatic Hénon-Heiles system (Hénon & Heiles 1964): (i) In some regions an adelphic integral of motion is present which hinders the particles on quasiperiodic orbits from escaping.…”
Section: Poincaré Surfaces Of Sectionmentioning
confidence: 83%
“…The following aspects are similarly found in the paradigmatic Hénon-Heiles system (Hénon & Heiles 1964): (i) In some regions an adelphic integral of motion is present which hinders the particles on quasiperiodic orbits from escaping.…”
Section: Poincaré Surfaces Of Sectionmentioning
confidence: 83%
“…2.4.3). The same comparison of the three particle Toda potential with its truncation, the Henon and Heiles potential [11], was very useful in understanding low-dimentional chaos, as we have already discussed briefly in Sect. 2.1.2.…”
Section: Chains Similar To the Fpumentioning
confidence: 92%
“…In particular, the KAM theorem for coupled degrees of freedom [8,9,10] indicated that the generic case was a divided phase space with regular and chaotic orbits interspersed. Numerical observations, in a surface of section of a particular two degree of freedom system (the Hénon and Heiles potential), indicated mostly regular orbits at low energy, with the chaotic portion of the phase space increasing rather abruptly over a small range of increasing energy, until most of the phase space is chaotic [11]. A practical explanation of this rather abrupt increase was that local resonances between frequencies of the two freedoms, which modified the structure of the phase space in their neighborhood, would overlap with increasing energy, producing large areas of chaotic motion [12,13].…”
Section: Chaos Theory: Kam Isolation Arnold Diffusion Lyapunov Expomentioning
confidence: 98%
See 1 more Smart Citation
“…Let us just give one example [31]. The Hamiltonian Hénon-Heiles system [62] in two coupled variables (q 1 , q 2 ) The diophantine equations to be solved are Three of them restrict the ODE to the stationary reduction of well-known soliton equations, thus proving the PP : Sawada-Kotera (SK [103]), higherorder Korteweg-de Vries (KdV5, [80]) and Kaup-Kupershmidt (KK, [71,51]) equations.…”
Section: The Diophantine Conditionsmentioning
confidence: 99%